1998
DOI: 10.1002/(sici)1097-4628(19980110)67:2<349::aid-app16>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Impact performance of phenolic composites following thermal exposure

Abstract: The notched and unnotched Izod impact properties of a series of phenolic‐glass composites following thermal exposure at 180°C, 300°C, and 800°C have been investigated. Four phenolic resins; a resol, a novolac, a resol/novolac blend, and a furan‐novolac/resol copolymer were used to prepare the composites. The notched and unnotched impact properties of all S‐glass composites improved following thermal exposure at 180°C for times up to 28 days. The best results at 180°C were obtained for the copolymer‐based compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…The change in the voltage was recorded with a digital voltmeter, which was online to the personal computer. The power output to the samples was adjusted according to the nature of the sample material and was, in most cases, in the range of 6 × 10 −6 to 16 × 10 −6 W/m 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the voltage was recorded with a digital voltmeter, which was online to the personal computer. The power output to the samples was adjusted according to the nature of the sample material and was, in most cases, in the range of 6 × 10 −6 to 16 × 10 −6 W/m 2…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the thermal transport properties of polymeric materials are important because of the crucial role played by these properties in both processing stages and product uses 1. The matrix resins for composites are used in structural applications2 and are widely used as industrial materials because of their good heat resistance, electrical insulation, dimensional stability, and flame and chemical resistance 3–8. Several reports9–12 have indicated that the incorporation of natural fibers into thermoset matrices improves the mechanical and thermal transport properties of the composites remarkably.…”
Section: Introductionmentioning
confidence: 99%
“…The Blend was prepared by using the resol to cure the novolac instead of using a crosslinking agent such as HMTA, the ortho and para hydroxyl groups of the novolac are active with respect to the methylol groups of the resol. Crosslinking at these sites leads to the cure of the Blend [7]. When HMTA is used, the Blend1 and linear novolac prepolymers are tightly crosslinked into a highly developed network, so the tan peak of Blend1 become a single peak from two peaks of the Blend.…”
Section: Mechanical and High-temperature Propertiesmentioning
confidence: 99%
“…The decline in the properties of the phenolic composite upon thermal ageing is due to the breakdown of the bonds at the fibre-matrix interface. The unnotched and notched izod impact performance of phenolic composites following thermal exposure was studied in detail by Kuzak et al [22]. They observed that the impact performance of the S-glass (Strength-glass) reinforced phenolic composite declined when exposed to 300 • C temperature.…”
Section: Ageing Effects On the Impact Propertiesmentioning
confidence: 99%